Development of Innovation Community Media to Prevent Emergency Medicine Among Community Dwellers Elderly - Sihapark, Siranee; Intaraphet, Suthida; Hanpatchaiyakul, Kulnaree (Journal of Health Sciences and Wellness, 2022)
This study was designed on a research and development approach and aimed to determine the development of originating the innovative community media for preventing emergency medicine among community-dwelling elderly people in Thailand which consisted of 1) the situation analysis and identifying factors related to medical emergencies among the elderly 2) development of the innovative community media to prevent medical emergencies for the elderly, and 3) the effectiveness evaluations of the innovative community media to prevent medical emergencies for the elderly, from January through December 2021. The findings were presented in three processes as follows: Firstly, elderly persons experiencing emergency services were having emergency crisis level nearly 20%. Also, associated factors were 6 factors included Asthma/COPD 8.065 (95%CI=2.383-27.302), CHD/chest pain 6.161 (95% CI = 3.132-12.119), diabetes 4.455 (95% CI = 2.084-9.523), hypertension 4.379 (95% CI = 95% CI = 2,450-2,949), pneumonia 3.945 (95%CI=2.152-7.233), and age ≥ 75 year 2.068 (95%CI=1.450-2.949). Moreover, the protective prevention factors were the early visiting and taking the ambulance Secondly, originating an innovative community media for preventing elderly people against emergency medicine. In this process, 1) to review factors that could be manipulated for preventing the elderly from emergency medicine, 2) to develop the innovative community media for preventing emergency medicine among elderly people that were concerned with the lifestyle of the elderly and the local wisdom, and 3) to evaluate the efficacy of the innovative community media. The results showed that the average satisfaction scores and the average knowledge scores on the innovative community media after training were significantly higher compared to before training. Furthermore, the efficacy of the innovative community media was higher than the established criteria. Finally, the health outcomes of innovative community media to prevent medical emergencies for the elderly after 3 months found that blood pressure levels and blood sugar of the elderly were significant at (P < 0.002) and (P < 0.004), respectively, and disease controls in the elderly with hypertension and diabetes were statistically significant at (P < 0.002) and (P < 0.007), respectively. Moreover, visiting the emergency department and exercise behavior were significant at (P < 0.001).